2017
DOI: 10.1515/znc-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the construction of insect P450 fusion enzymes

Abstract: Cytochrome P450 monooxygenases (P450s) are ubiquitous enzymes with a broad substrate spectrum. Insect P450s are known to catalyze reactions such as the detoxification of insecticides and the synthesis of hydrocarbons, which makes them useful for many industrial processes. Unfortunately, it is difficult to utilize P450s effectively because they must be paired with cytochrome P450 reductases (CPRs) to facilitate electron transfer from reduced nicotinamide adenine dinucleotide phosphate (NADPH). Furthermore, euka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Moreover, this depletion could be reversed by treatment of cells with the CYP707A inhibitor, abscinazole‐E3M. The majority of CYP enzymes require the assistance of NADPH‐cytochrome P450 reductase for the electron transfer from NADPH [40]. However, the overexpressed AtCYP707A3 depleted ABA in HEK293T cells without expressing additional CYP reductase, indicating the involvement of endogenous CYP reductase.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this depletion could be reversed by treatment of cells with the CYP707A inhibitor, abscinazole‐E3M. The majority of CYP enzymes require the assistance of NADPH‐cytochrome P450 reductase for the electron transfer from NADPH [40]. However, the overexpressed AtCYP707A3 depleted ABA in HEK293T cells without expressing additional CYP reductase, indicating the involvement of endogenous CYP reductase.…”
Section: Resultsmentioning
confidence: 99%
“…According to the branching situation, C. buqueti and Dendroctonus ponderosae are more closely related, but compared with the red-brown weevil, C. buqueti is more closely related to the latter. The red palm weevil is a pest that is seriously harmful to palm plants [ 34 ] ,whose larvae feed on the main stem cause irreversible damage to the host plant and severely cause plant death in the short term [ 5 ] Studies have shown that it is the most destructive pest of palm trees worldwide, and functional analysis has demonstrated that the up-regulation of P450 gene expression has evolved into adaptation to insecticide stress caused by exposure to the systemic neonicotinoid insecticide imidacloprid [ 35 ]. C. buqueti is most closely related to Rhynchophorus ferrugineus , and it is speculated that the large C. buqueti has the same relationship with insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular basis for the transcriptional regulation of Cytochrome P450 remains largely unknown [ 4 ]. Studies have shown that it is difficult to utilize P450 effectively now because they must be paired with cytochrome P450 reductase (CPRs) to facilitate electron transfer from reduced nicotinamide adenine dinucleotide phosphoric acid (NADPH) [ 5 ]. Insects are the most prosperous biological population on the earth, the role of P450 involves insect growth, development, feeding and other processes, it is also involved in the synthesis and metabolism of many endogenous compounds in insects, and metabolic detoxification is one of the important functions of the enzyme system.…”
Section: Introductionmentioning
confidence: 99%
“…To note, some evidences from non‐mosquito insects (e.g., most studied Drosophila melanogaster fruit fly) could be suggestive for the strategies of efficient in vitro P450 expression or fusion enzyme construction 62,63 for in vitro studies of vector CYPs. Other interesting studies regard mitochondrial CYP12A4 and CYP12D1 involvement in Drosophila insecticide resistance 64,65 or detoxification enzyme targeting in Spodoptera littoralis 66 …”
Section: Malariamentioning
confidence: 99%